Outcomes in the management of esophageal cancer. Issue 5 (21st August 2014) - Paul, Subroto; Altorki, Nasser; Greene, Frederick L.; Rosen, Jennifer E.
Abstract Esophageal cancer rates have continued to rise in the Western World. Esophageal cancer will be responsible for an estimated 15, 450 deaths in the United States in 2014 alone. Esophageal resection with or without preoperative therapy remains the mainstay of treatment. Advances in surgical technique and perioperative care have improved short‐term outcomes considerably by decreasing operative mortality. Despite these advances though, esophagectomy remains a procedure associated with considerable morbidity from a wide range of complications. Prompt recognition and treatment of complications can lower overall morbidity and mortality. Unfortunately, long‐term outcomes remain poor as the vast majority of patients present with loco‐regionally advanced or metastatic disease. Surgery by itself provides poor loco‐regional control and fails to address micrometastatic disease. Neoadjuvant chemotherapy or chemoradiation provides a modest survival advantage compared to surgical resection alone. Future gains in understanding the molecular biology of esophageal cancer will hopefully lead to improved therapeutics and resultant outcomes. J. Surg. Oncol. 2014 110:599–610. © 2014 Wiley Periodicals, Inc.